A current-driven nanometer water pump. (29th January 2016) - Su, Jiaye; Yang, Keda
Abstract: The design of a water pump, which has huge potential for applications in nanotechnology and daily life, is the dream of many scientists. In this paper, we successfully design a nanometer water pump by using molecular dynamics simulations. Ions of either sodium or chlorine in a narrow channel will generate electric current under electric fields, which then drives the water through a wider channel, similar to recent experimental setups. Considerable water flux is achieved within small field strengths that are accessible by experimentation. Of particular interest, is that for sodium the water flux increases almost linearly with field strengths; while for chlorine there exists a critical field strength, the water flux exhibits a plateau before the critical value and increases linearly after it. This result follows the behavior of ion velocity, which is related to friction behavior. We also estimate the power and energy consumption for such a pump, and compare it to the macroscopic mechanical pumps. A further comparison suggests that different ions will have different pumping abilities. This study not only provides new, significant results with possible connection to existing research, but has tremendous potential application in the design of nanofluidic devices.